Bentuk Penyajian Suling Bambu Dalam Tradisi Balahak Di Desa Koto Periang Kecamatan Kayu Aro Kabupaten Kerinci - Elgi Jet Forgano; Wimbrayardi Wimbrayardi (FBS Universitas Negeri Padang, 2021)
This research aims to describe the Form of Bamboo Distilled Presentation in Balahak Tradition in Koto Periang Village, Aro Wood District Kerinci Regency. Qualitative research method that aims to get everything related to the topic. Data collection is done by library study techniques, observations, interviews and documentation. Distilled Bamboo art is a native art of kerinci people that reflects the social life of its people and develops in the community of Koto Periang Village which is displayed in balahak tradition. Balahak in indonesian synonym equal to procession, defile, kirab, convoy, parade is traveling together or accompaniment regularly with one purpose in a series of traditional, religious and so on ceremonies. Balahak started the groom to the bride's house, on the way the player Distilled Bamboo played the song Nasib Malang with several pantuns over and over before getting to the bride's house. After that it again started for the two brides around the village, The Bamboo Flute Player played and the vocalist sang the song wahai pemuda dan Indonesia until returning to the bride's house.